Pediatric Gunshot Head Injury: Prevalence of Prognostic Factors in Surgical Patients: An Institutional Experience in Ten Years - Luiz Severo Bem Junior; Ot?vio da Cunha Ferreira Neto; Art?mio Jos? Araruna Dias; Pedro Lukas Do R?go Aquino; Jos? Renan Miranda Cavalcante Filho; Andrey Maia Silva Diniz; Lu?s Felipe Gon?alves de Lima; Nilson Batista Lemos; Joaquim Fechine de Alencar Neto; Thais Lima Da Silva; Taciana Andrade De Abreu; Jo?o Guilherme De Lima Guerra Barros; et al. (Neurotrauma Reports, 2021)
This article aims to evaluate the predictive factors of morbidity and mortality in pediatric patients who suffered gunshot wounds to the head. We reviewed a series of 43 patients who were admitted to a referential neurosurgical hospital between 2010 and 2019. Data from 43 patients who underwent a surgical treatment in our institution were collected, and the following parameters were considered in the analysis: the initial Glasgow Coma Scale (GCS), age, sex, bullet entry site, and bullet trajectory. Computed tomography (CT) scans at admission, complications, midline crossing, and Glasgow score scale at the time of discharge (Glasgow Outcome Scale; GOS) were also factored in. Male sex corresponded to 90.7% of cases (N?=?39), and 16?17 years of age was the most common age (60.5%). The frontal region was the most common entry site (41.9%), followed by the parietal wall and occipital entry. Penetrating trajectory was shown in 48.8% of cases, perforation/transfixing in 39.5%, and tangential in 11.6%. CT showed that sinking is the most common alteration (74.4%), followed by cerebral contusion (44.2%). According to the GOS, 23.3% died, 23.3% were classified by an unfavorable outcome (GOS, 2?3), and 53.5% a favorable outcome (GOS, 4 and 5). In our study, there was a significant association between the low GCS scores on admission and low GOS (1?3; p?=?0.001) at time of discharge. Patients with wounds that crossed the midline also had a significant association with low GOS (p?=?0.014) in our clinical experience. We concluded that low GCS scores at admission and children with a wound that crosses the midline are predictive factors of high mortality and morbidity, in our clinical experience.